Intake of added sugar, fruits, vegetables, and legumes of Portuguese preschool children: Baseline data from SmartFeeding4Kids randomized controlled trial participants - Charneca, Sofia; Gomes, Ana Isabel; Branco, Diogo; Guerreiro, Tiago; Barros, Luísa; Sousa, Joana (Frontiers in Nutrition, 2023)
The SmartFeeding4Kids (SF4K) program is an online self-guided intervention for parents with the propose of changing parental feeding practices and children’s dietary intake, focusing on the intake of added sugars, fruit, vegetables, and legumes. This paper aims to describe children’s dietary pattern at baseline through a 24-hour food recall, the SmartKidsDiet24. Overall, 89 participants recorded at least one meal of the 3-day food recall. Mean age was 36.22±6.05 years and 53.09±15.42 months old for parents and children, respectively. Of these, 22 participants were considered to have 2 days of near complete 24-hour food recalls (theSmartKidsDiet24). Children’s dietary intake are reported for these 22 participants based on parents reports and, thus, represent estimations only, as it remains unknown whether children consumed other non-reported foods. Fruit was the group with the highest daily intake among children (mean 1.77±1.10 portions/day), followed by added sugar foods (mean 1.48±0.89 portions/day), vegetables (median 1.27 (1.64) portions/day) and legumes (median 0.12 (0.39) portions/day). Fruit intake was positively correlated with vegetable intake (p=0.008). Regarding Dietary Reference Values accomplishment, 13.6% of children exceeded the daily safe and adequate intake of sodium, 77.3% did not meet potassium and fiber recommendations, and 31.8% did not meet vitamin C recommendations. All children did not meet calcium, vitamin B12 and vitamin D intake recommendations. Our findings further justify the need for dietary interventions in this field, to improve young children’s diets.